GSK3 inhibitor enhances gemtuzumab ozogamicin‐induced apoptosis in primary human leukemia cells by overcoming multiple mechanisms of resistance. Issue 1 (12th December 2022) - Inase, Aki; Maimaitili, Yimamu; Kimbara, Shiro; Mizutani, Yu; Miyata, Yoshiharu; Ohata, Shinya; Matsumoto, Hisayuki; Kitao, Akihito; Sakai, Rina; Kawaguchi, Koji; Higashime, Ako; Nagao, Shigeki; et al.
Abstract: In acute myeloid leukemia (AML), the heterogeneity of genetic and epigenetic characteristics makes treatment difficult. The prognosis for AML is therefore poor, and there is an urgent need for new treatments for this condition. Gemtuzumab ozogamicin (GO), the first antibody‐drug conjugate (ADC), targets the CD33 antigen expressed in over 90% of AML cases. GO therefore has the potential to counter the heterogeneity of AML patients. However, a major clinical problem is that drug resistance to GO diminishes its effect over time. Here, we report that the inhibition of glycogen synthase kinase 3 (GSK3) alone overcomes several forms of GO resistance at concentrations without antileukemic effects. The GSK3 inhibitors tested significantly enhanced the cytotoxic effect of GO in AML cell lines. We elucidated four mechanisms of enhancement: (1) increased expression of CD33, the target antigen of GO; (2) activation of a lysosomal function essential for hydrolysis of the GO linker; (3) reduced expression of MDR1 that eliminates calicheamicin, the payload of GO; and (4) reduced expression of the anti‐apoptotic factor Bcl‐2. A similar combination effect was observed against patient‐derived primary AML cells. Combining GO with GSK3 inhibitors may be efficacious in treating heterogeneous AML.